1998
DOI: 10.1577/1548-8675(1998)018<0587:aisfpf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated System for Production Fish Aging: Image Analysis and Quality Assurance

Abstract: There is an increasing demand for aging data to provide inputs to stock assessment models for management of exploited fish populations. Image analysis software and computer hardware allow more rapid processing of samples and data. This paper describes a fully integrated system that has been in operation for 5 years and has been used to provide age estimates for more than 150 species. The system combines the requirements of high‐quality “production” aging with the benefits of a customized image analysis system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 19 publications
3
61
0
1
Order By: Relevance
“…We subsequently sought to validate age estimates from sectioned otoliths using more stringent validation procedures (Francis et al 1992;Francis 1995;Morrison et al 1998). Otoliths from recaptured fish in both streams were embedded in epoxy resin and sectioned transversely (0.60 mm width) through the nucleus along the dorso-ventral plane (Chilton and Beamish 1982).…”
Section: Sectioned Otolithsmentioning
confidence: 99%
“…We subsequently sought to validate age estimates from sectioned otoliths using more stringent validation procedures (Francis et al 1992;Francis 1995;Morrison et al 1998). Otoliths from recaptured fish in both streams were embedded in epoxy resin and sectioned transversely (0.60 mm width) through the nucleus along the dorso-ventral plane (Chilton and Beamish 1982).…”
Section: Sectioned Otolithsmentioning
confidence: 99%
“…Increment widths were measured in sagittae (the largest set of otoliths) that had been embedded, sectioned to expose the innermost increments, and examined under transmitted light microscopy. Increments were measured with a digital image analysis system (11). The number of clearly ''readable'' increments that could be consistently measured in a species varied among them, from the interior-most two to five increments (corresponding to growth over the course of 2-5 years, respectively; Table 1), which delimited the juvenile period we were able to examine in each species.…”
mentioning
confidence: 99%
“…Otolith weight in this study showed an inflexion point between 184 and 200 mm of TL, which seems to coincide with the length of sexual maturation of the tilapias. Morison et al (1998) mentioned an inflexion point in otolith weight at around the age of maturity. Despite the proven value of previous age determination studies of tilapia species using otoliths (Booth et al 1995, Booth and Merron 1996, Weyl and Hecht 1998, Admassu and Casselman 2000 opercula (Jiménez-Badillo 2004) and annuli in scales (Moreau 1971, Wosnitza-Mendo 1980, Yamaguchi et al 1990), these studies were performed on fish from the wild.…”
Section: Discussionmentioning
confidence: 99%